Acceptability of locally produced ready‐to‐use therapeutic foods in Ethiopia, Ghana, Pakistan and India. Issue 2 (18th January 2016) - Weber, Jacklyn M.; Ryan, Kelsey N.; Tandon, Rajiv; Mathur, Meeta; Girma, Tsinuel; Steiner‐Asiedu, Matilda; Saalia, Firibu; Zaidi, Shujaat; Soofi, Sajid; Okos, Martin; Vosti, Stephen A.; Manary, Mark J.
Abstract: Successful treatment of severe acute malnutrition has been achieved with ready‐to‐use therapeutic food (RUTF), but only 15% of children with severe acute malnutrition receive RUTF. The objective of this study was to determine whether new formulations of RUTF produced using locally available ingredients were acceptable to young children in Ethiopia, Ghana, Pakistan and India. The local RUTFs were formulated using a linear programming tool that allows for inclusion of only local ingredients and minimizes cost. The study consisted of 4 two‐arm, crossover, site‐randomized food acceptability trials to test the acceptability of an alternative RUTF formula compared with the standard peanut‐based RUTF containing powdered milk. Fifty children with moderate wasting in each country were enrolled in the 2‐week study. Acceptability was measured by overall consumption, likeability and adverse effects reported by caregivers. Two of the four RUTFs did not include peanut, and all four used alternative dairy proteins rather than milk. The ingredient cost of all of the RUTFs was about 60% of standard RUTF. In Ethiopia, Ghana and India, the local RUTF was tolerated well without increased reports of rash, diarrhoea or vomiting. Children consumed similar amounts of local RUTF and standard RUTF and preferred them similarly as well. In Pakistan, local RUTF was consumed in similar quantities, but mothers perceived that children did not enjoy it as much as standard RUTF. Our results support the further investigation of these local RUTFs in Ethiopia, Ghana and India in equivalency trials and suggest that local RUTFs may be of lower cost.